2019
DOI: 10.2478/hukin-2019-0116
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-Determined Motivation, Team Potency, and Self-Talk in Team Sports

Abstract: The current study aimed to evaluate the determinant factors of athletes´ internal positive self-talk that might lead to decreased anxiety and increased performance. The sample consisted of 191 male and female athletes ranging in age from 14 to 35 years old. They played soccer, volleyball and basketball and they were cadets (43%), juniors (29.6 %) and adults (27.4%). Results showed that satisfaction of the basic psychological needs was the strongest predictor of positive self-talk or positive thoughts during co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
9
0
2
Order By: Relevance
“…Furthermore, the results showed that the satisfaction of the needs for autonomy and relatedness were positively related to positive self-talk and negatively related to negative selftalk; whereas the thwarting of the needs for competence and relatedness was positively associated with students' negative self-talk and negatively related to positive self-talk. Regarding need satisfaction, the above results are in line with the previous research examining the links between self-talk and BPNs' satisfaction [44].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the results showed that the satisfaction of the needs for autonomy and relatedness were positively related to positive self-talk and negatively related to negative selftalk; whereas the thwarting of the needs for competence and relatedness was positively associated with students' negative self-talk and negatively related to positive self-talk. Regarding need satisfaction, the above results are in line with the previous research examining the links between self-talk and BPNs' satisfaction [44].…”
Section: Discussionsupporting
confidence: 90%
“…Based on other studies, a decrease in the coach's self-control may lead to a lower satisfaction of the athletes' need for competence [56]. In this line, a decrease in the perception of support in the need for competence has implications on the athlete's competitive capacity, as it predicts the athlete's confidence in relation to sports performance [57].…”
Section: Discussionmentioning
confidence: 95%
“…Positive self-talk has been used extensively in the sports world, and places emphasis on attention control, increasing concentration, and reducing anxiety, with a view to challenging irrational beliefs [ 25 ]. Self-talk is becoming an increasing popular tool in health care.…”
Section: Emotional Balancementioning
confidence: 99%